GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 533760002 species occurrences available in GBIF matching the query: All data. The dataset includes 533760002 records from 13036 constituent datasets: 5 records from Wanninchen. 979 records from Herbier_CNSF. 14165 records from NYSM Mammals. 1990 records from Seabird 2000. 1 records from Heckenstreifen am Zehntbergweg. 92 records from Wiesen in der Grünen Mitte. 31 records from Regenwasserabfangbecken. 198287 records from IBF Monitoring of Vascular Plants. 479 records from CBS Bacteria Database. 1833 records from DSMZ Fungi. 144 records from Lustbach-Umland. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 27975 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 373 records from Otter survey of Ireland 2004 & 2005. 1238 records from Insect Collection (CeStuBio). 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 21188 records from National Bat Database of Ireland. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 40 records from Schulhof Liebfrauenschule Oldenburg. 27 records from Zwickau- Schwanenteich. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 8565 records from Herpetology. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 936 records from Bats of Poland. 397 records from Danish Lacewings (Neuroptera). 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 28 records from Hainbachtal bei Oelsnitz / V.. 102 records from BIRDRACE Westfälische Nachtigallen. 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 2486 records from Hawaiian Algal Database. 194 records from Total foraminifera counts from multinet M32/3_MSN958. 495463 records from Field Museum of Natural History (Zoology) Bird Collection. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 1000 records from Mollusca Specimens of Oiso Municipal Museum. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 101 records from Hoher Stein Kallenhardt. 54 records from Total foraminifera counts from M35/1_MSN1057. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/049-3. 18 records from Phytoplankton abundance at station Rigel_6_2005-04 in April 2005, Chipana, Chile. 482 records from Kühmark bei Wetzlar. 8 records from Ostracoda abundance of Hole 42-375. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 195867 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 114 records from Birdrace-Finkenspötter-München. 92 records from Birdrace-Team_BO-bachter-Bochum. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 122 records from Stever. 5 records from Schulinnenhöfe (Gelsenkirchen). 269 records from BIRDRACE Dithmarscher Deichhühner. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 63 records from Erft in Selikum (Neuss). 128 records from Birdrace_turbine_untersee-Konstanz. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 66 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, 63-150 µm. 75 records from Faunal assemblage of sediment core GS7603-9. 133 records from Total foraminifera counts of multinet M42/3_MSN1363. 87 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1363. 122 records from Phytoplankton abundance at station CD46_1005C#4. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 261 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Orthoptera Records up to Dec 2012. 29 records from Schulaktion des Dienzenhofer-Gymnasiums. 56 records from Nanoplankton abundance at station GeoB2021-3. 3 records from Nannofossil abundance of Hole 31-301. 2 records from Nannofossil abundance of Hole 3-21A. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 1565 records from (Table 1) Calcareous nannofossil distribution at ODP Site 180-1109 from the Solomon Sea, western Pacific. 6325 records from Colección Entomológica de la Universidad de Antioquia. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 3 records from Nannofossil abundance of Hole 94-609A. 694 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 225 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE262. 115 records from Mollusca specimens of Kuroshio Biological Research Foundation. 20114 records from Molluscus specimens of Toyohashi Museum of Natural History. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 94 records from Plasm bearing foraminifera counts from M35/1_MSN1044. 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 181 records from Total foraminifera counts of multinet M21/6_MSN766. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 49 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/514-18. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 370 records from Size of planktic foraminifera at CTD station PS55/051. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 290 records from Planktic foraminifera counts of sediment core RC11-134. 100733 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 228 records from Total foraminifera counts from multinet M31/3_MSN917. 11 records from Plasm bearing foraminifera counts from multinet M31/2_MSN896. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 76 records from Total foraminifera counts of multinet M36/2_MSN1107. 29 records from Counts (1) of calcareous dinocysts along profile Stevns-Klint. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 823 records from Planktic foraminifera counts of sediment core V17-165. 1139 records from Shellfish (MNHM-MS). 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_832-7. 9 records from Microzooplankton abundance and biomass at station TT043_6-1. 19 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_7-CTD84. 9 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 54223 records from Fish Specimens. 48 records from Nanoplankton abundance at station GeoB2005-5. 11 records from Nannofossil abundance of Hole 10-86. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 89 records from (Table 3) Dinoflagellate cysts from sediment profile PS1730. 42920 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 10189 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 8944 records from N3 data of Kiel bay (EurOBIS). 2257 records from South Western Pacific Regional OBIS Data Asteroid Subset (South Western Paci fic OBIS). 9281 records from Distribution of planktic foraminifers of core V30-40. 3 records from Analyses of the recent components of sediment core PS1215-2. 316 records from Moss species from Heard Island, 1987 and 2000. 8 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/108-1. 2 records from Composition of the larger coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 11 records from Benthic macrofauna abundance of sediment core 13077-087. 316 records from Planktic foraminifera counts of sediment core V14-101. 936 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 801 records from Collection Porifera - ZMB. 339 records from (Table 6) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 1289 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 10928 records from TRTE Herbarium (TRTE). 114357 records from Data on moths from automatically operating light traps in Denmark. 44 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE293. 9 records from Component analysis of TV-guided grab sampler GeoB10071-3. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 1422 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 18 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 5 records from Bryophyte Collection of Shizuoka Prefecture Museum of Natural History. 4433 records from Röntgenarchiv Wilhelm Stürmer - SMF. 15328 records from SOMBASE. 60445 records from Bureau of Rural Sciences National commercial fisheries half-degree data set 2000-2002 (OBIS Australia). 600 records from (Table 2) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 1534 records from Pontaurus. 100 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A. 50 records from (Table 4) Abundances of dinoflagellates in DSDP Hole 81-552A. 432 records from (Table 3) Occurrence of dinocyst species in ODP Hole 113-692B. 119 records from Palynology of a sediment profile from Lake Voulkaria in Greece. 560 records from (Table 3h) Foraminiferal distribution chart of petroleum well Swan-3St. 2073 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 5804 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 6019 records from iziko South African Museum - Mollusc Collection (AfrOBIS). 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 6450 records from Meiobenthos of subtidal sandbanks on the Belgian Continental Shelf (EurOBIS). 63084 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1996) (AfrOBIS). 126 records from Kelp rafts in the Southern Ocean. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 1194 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-29. 234 records from Danisco-Wiese. 80 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 61 records from Steinbruch Pluwig. 67725 records from Patterns of widespread decline in North American bumble bees. 1048 records from Biodiversidad y dinámica espacio-temporal del ictioplancton de dos sistemas lagunares de la Reserva de la Biósfera de Sian Ka'an. 3538 records from Anfibios del Estado de Veracruz.. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 1611 records from Percentages of planktonic foraminifera species in sediment core RC13-189. 897 records from Diatom and foraminiferal samples from surficial sediments of Prydz Bay, Antarctica. 2500 records from Zooplankton (NSMK-ZP). 2 records from Akita Prefectural Museum＋Specimens of Phylum Porifera of Akita Prefectural Museum. 2427 records from Ibaraki Nature Museum, Mollusk collection. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 367 records from ARKO. 10 records from (Table 3) Cell number of the main taxonomic groups of phytoplankton and their percentage in total number of phytoplankton in the water column in the northern subtropical Pacific. 180 records from (Table 8) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-217. 1202 records from (Table 18) Ranges of benthic foraminifers through the Neogene in DSDP Hole 23-219. 2054 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of DSDP Hole 38-338. 237 records from Collection Mammalogie - SNSD. 1 records from Pelops tardus. 11209 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 29 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Baerbel Bleher. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 7121 records from MUST, Insecta. 21243 records from Myxomycetes Collection of National Museum of Nature and Science. 940 records from Planktic foraminifera distribution of sediment core CS72-37. 58 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV24. 878 records from Planktic foraminifera abundance of Hole 84-568. 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 10591 records from Planktic foraminifera (%) of sediment core MD97-2151. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 5 records from Analyses of the recent components of sediment core PS1400-4. 1036 records from Benthic foraminifera distribution of sediment core ASV1200. 15312 records from UCM Mammal Collection (Arctos). 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 92 records from Nottekanal, Klasse 7 - 10. 640 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 1339 records from Percentages of planktonic foraminifera species in sediment core V25-75. 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1003 records from BÜG. 224 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 214 records from Mißmahlsche Anlage. 65 records from Occurrence of mammalia relicts at site L´Abri Duruthy. 19 records from Occurrence of mammalia relicts at site Vraona Cave. 796 records from Planktic foraminifera abundance of Hole 42-372. 692 records from Planktic foraminifera abundance of Hole 40-360. 201 records from Planktic foraminifera abundance of Hole 32-313. 52 records from Range table from planktonic foraminifers in ODP Hole 151-913A. 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 877 records from Benthic foraminifera abundance of Hole 40-362. 76 records from Range table from benthic foraminifers in ODP Hole 139-856A. 133 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 13 records from Occurrence of mammalia relicts at site Trou du Renard. 163 records from Range table from planktonic foraminifers in ODP Hole 175-1083A. 405 records from Freiburger Netzwerk Artenvielfalt. 2 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 1 records from Nothrus angulatus. 25128 records from Royal Museum of Central Africa - Albertian Rift Butterflies (ENBI wp13). 7585 records from National Barkfly Recording Scheme - Outdoor Psocoptera (barkfly) records for Britain & Ireland, 1850 to present.. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 22 records from Occurrence of mammalia relicts at site Igrita Cave. 74 records from Planktic foraminifera abundance of Hole 62-465A. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 12 records from Phytoplankton abundance in surface water in October 1995, Chimbote, Peru. 228 records from Phytoplankton abundance in surface water in June 1997, Pisco, Peru. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 11 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 19 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mar del Plata (Pugnali, junio 1998). 74 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 62 records from Occurrence of mammalia relicts at site Zawalona Cave. 12 records from Planktic foraminifera abundance of Hole 14-138. 73 records from Planktic foraminifera abundance of Hole 2-11. 332 records from Planktic foraminifera abundance of Hole 9-79. 70 records from Planktic foraminifera abundance of Hole 84-569A. 518 records from Foraminifera abundance of Hole 21-208. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 3630 records from Benthic foraminifera distribution of sediment core GIK17957-2. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 25 records from (Fig. 9B) Compiled data of profile Pré-Guittard, SE France. 1182 records from (Appendix A3) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1212B in the central Pacific. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 28420 records from Lichen Collection - University of Washington Herbarium (WTU). 1 records from Abundance of benthos infauna at station GIK23004-3. 122571 records from Herbier de la Guyane. 1137 records from Plantas Acuáticas de la Orinoquía Colombiana. 85449 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 72636 records from Insect Collection of Taiwan Forestry Research Institute. 5778 records from Vascular Herbarium, NMBU. 26 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto48-56. 1 records from Zetes latirostris. 157 records from (Table 6) Live benthic foraminifera in sediment core SO130-291MC. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 864 records from (Table T16) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P9-P12. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 5468 records from Orchid Herbarium Collection. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 743 records from Fish monitoring data in Lake Kasumigaura. 89874 records from ecoscope_observation_database. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 9787 records from Finnish Entomological Database: Hymenoptera. 76 records from BIRDRACE Nachtigallen. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 4599 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from New species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Côte d’Ivoire. 8629 records from National Taiwan University. 267 records from Die Milbenfauna der Nordseeinsel Wangerooge. 27278 records from UAM Entomology Observations (Arctos). 9024 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 246960 records from Vascular Plants, Field notes, Trondheim (TRH). 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 76 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 127 records from Kieppi mammals collection. 755 records from Helgeland Museum, Syrphidae. 21 records from Occurrence data of Namibimydas and Nothomydas (Diptera: Asiloidea: Mydidae). 3275 records from Quantitative Phytoplankton data from Irish lakes (EPA). 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 9349 records from Harriet Irving Botanical Gardens (HIBG). 16098 records from The Bat Conservation Trust - The BCT/MTUK Bats & Roadside Mammals Survey. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 63 records from (Data S1) Palynology of ODP Site 119-739. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 57 records from Waldhusener Moor (Lübeck-Kücknitz). 39 records from Stausee Weiditz. 84 records from Total foraminifera counts of multinet M12/3_MSN538. 68 records from Plasm bearing foraminifera counts of multinet M21/5_MSN729. 22 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1337. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 4 records from A new platygastrid wasp from Florida (Hymenoptera: Platygastridae).. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 4024 records from Sightings Map of Invasive Plants in Portugal. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 20043 records from Mollusca collection of National Museum of Nature and Science. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 1 records from Oribates picipes. 18940 records from Cowan Tetrapod Collection - Mammals. 155255 records from CAS Invertebrate Zoology (IZ). 400 records from Colección Limnológica del Chocó. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 3204 records from Faunal Inventory of Morysin Nature Reserve. 177466 records from CAS Entomology (ENT). 2172 records from Coleccin de Reptiles. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 28370 records from UAM Bird Collection (Arctos). 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records . 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 1 records from Nothrus bicarinatus. 3387 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 5155977 records from Australia's Virtual Herbarium. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 42 records from sbosch. 138 records from Plasm bearing foraminifera counts from multinet SO119_MSN1278. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_1-CTD14. 5 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC7. 46 records from 8c. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 202 records from Total foraminifera counts from multinet M31/3_MSN900. 881 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 70 records from Planktic foraminifera counts of sediment core RC13-153. 213 records from Amphibian and Reptile (JNHM-AR). 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 8095 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 114 records from Flora. 107 records from Landschaftsschutzgebiet Buchhorst 3. 244 records from WildesMoor bei Schwabstedt. 49 records from Dörnberg. 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 89 records from Schulgelände Paul-Gerhardt-Schule. 371 records from Bannwald Burghauser Forst. 101 records from Steinbruch Kronungen. 12 records from Art´n Vielfalt im Kinderwald. 1770 records from Schmidt Museum of Natural History_Birds. 233 records from Total foraminifera counts from multinet M32/5_MSN976. 124 records from Total foraminifera counts of multinet M12/3_MSN559. 50 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1338. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 82 records from BIRDRACE Die Ziegeneier. 61 records from BIRDRACE Baumläufer. 3895 records from Colección de mamíferos de la Universidad del Valle. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 81 records from Total foraminifera counts of multinet M21/5_MSN728. 239 records from Size of planktic foraminifera at CTD station M39/4_376CTD-29. 6 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 66 records from Calcareous dinoflagellates nominated in grain fraction < 20 µm. 126 records from Mol·luscs d'Andorra. 18 records from Phytoplankton abundance at station Rigel_4_2005-04 in April 2005, Chipana, Chile. 127 records from Meiobenthic assemblages colonizing artificial soft sediments at 20 m depth in Arctic glacial Kongsfjorden, Spitsbergen, Svalbard - individual number. 9 records from Trap data GBN3, 3921 m. 10 records from Microzooplankton abundance and biomass at station TT045_21-25. 1 records from Microplankton counts and carbon biomass at station TT008_6-CTD64. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 40 records from Nannofossil abundance of Hole 47-398. 6 records from Nannofossil abundance of Hole 4-30. 74 records from Ostracoda abundance of Hole 48-401. 2 records from Nannofossil abundance of Hole 74-526C. 6 records from Microzooplankton abundance and biomass at station NBP97-08-31-7. 36 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 18 records from Phytoplankton abundance during G. M. Dannevig cruise GMD91/10. 138 records from Fig. 3. Pollen counts of the PG1756 core from Lake Billyakh. 345 records from Cretaceous nannofossils in profile Serre Chaitieu, SE France. 4 records from Nannofossil abundance of Hole 16-156. 248680 records from Swiss National Orthoptera Databank. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 69 records from Mönchspark. 14 records from Nannofossil abundance of Hole 49-412. 9 records from Diatom abundance measured on water bottle samples at station PS58/048-3. 1127 records from Planktic foraminifera counts of sediment core RC14-35. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 61 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/362-1. 1351 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 326 records from Planktic foraminifera counts of sediment core V14-77. 55189 records from UWBM Mammalogy Collection. 569 records from Distribution of nanoplankton at trap WR2. 51 records from Coccoliths in sediment core PS1295-4. 26 records from Ostracoda abundance of Hole 13-132. 2 records from Nannofossil abundance of Hole 6-57A. 55 records from Nannofossil abundance of Hole 94-609. 79 records from Ostracoda abundance of Hole 34-319. 24 records from Nannofossil abundance of Hole 8-72. 73 records from Nannofossil abundance of Hole 3-15. 22 records from Nannofossil abundance of Hole 39-355. 7 records from Nannofossil abundance of Hole 27-259. 14 records from Nannofossil abundance of Hole 14-140. 758888 records from Flora Atlas N.T.. 13 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/046-3. 51 records from Nannofossil abundance in sediment core PS1293-4. 414 records from (Table A a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-22 at 2000 m water depth. 160 records from (Table 5) Distribution of Pleistocene to late Oligocene nannofossils in ODP Hole 108-659A. 565 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_2. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 671604 records from LACM Vertebrate Collection. 144 records from (Table 7) Distribution of ostracode species in surface sediments of the central Laptev Sea. 785 records from (Appendix I) Distribution of Quaternary nannoflora at DSDP Site 90-594 east of South Island, Southwest Pacific. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 18 records from Meiofauna abundance in sediment core 13368-015. 90 records from Planktic foraminifera counts of sediment core RC13-158. 69 records from Planktic foraminifera counts of sediment core V19-19. 129 records from Dinoflagellate cysts from sediment core PS2458-4. 20691 records from Cladocera and Copepoda. 146133 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 6256 records from Colección Ictiológica del Río Bravo en México (UANL). 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 61 records from BIRDRACE Bergische Ornis. 118 records from Antarctic Amphipoda. 48 records from Abundance of phytoplankton in surface water during THALASSA campaign PROSOPE. 204 records from Dinoflagellates and pollen of the Brito-Arctic Igneous Province flora, ODP Hole 104-642E. 40 records from Pollen record of sediment core Bokanjacko Blato 1. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 270 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 21296 records from Nearctic Spider Database. 307 records from Schlichemquelle (Tieringen/Meßstetten). 882 records from Occurrence of mammalia relicts at site Pestera la Adam. 4917 records from (Table 1) Distribution of planktonic and selected benthic foraminifers from DSDP Site 87-582. 40 records from Planktic foraminifera abundance of Hole 14-137. 49812 records from Seaweeds of Ireland. 4203 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 108 records from (Fig. 9g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2041. 4 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 3918 records from Reptiles del Estado de Veracruz.. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 16233 records from Crustacea specimens of Toyama Science Museum. 22 records from (Table 18) Nannoplankton distribution in sediment core ANS3-T6. 72 records from (Table 1) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-682A. 429 records from Larval fish at Helgoland Roads in 2004. 478 records from Parásitos de peces nativos de cenotes de la Península de Yucatán, un ecosistema único en México. 299 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 573 records from Macrobenthic species of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 31082 records from MEXU/Plantas Vasculares. 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 609 records from Herbier L. Mulon (BOUM). 18 records from (Table 10) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-686. 51438 records from Dinoflagelados y Diatomeas del Pacífico tropical mexicano. 181 records from Marine Biological Association - RISC and ALERT Marine Non-Native Species (Chinese Mitten Crab, Wakame and Carpet Sea Squirt) Records. 150169 records from UWFC Ichthyology Collection. 13195 records from Fish Collection of Natural History Museum and Institute, Chiba. 67661 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1994) (AfrOBIS). 430 records from Mammifères sauf Chiroptères du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 769 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 275 records from Range table from benthic foraminifers in ODP Hole 198-1209A. 863 records from (Table 2) Distribution chart of dinoflagellate cysts and acritarchs from Angles, Southeast France. 9647 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 764 records from Foraminifera abundance of sediment core AC85-4. 284 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 289 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 75 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 607514 records from Plant. 463 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 1634 records from (Table 2) Stratigraphic occurrences of the dinoflagellate cysts in lithologic Subunit IIIB of ODP Hole 120-748C. 310 records from (Table S1) Dinoflagellate cysts, pollen and spores of sediment core ABC26. 2368 records from Collection Crustacea - SNSD. 19760 records from Danish waterbugs (Insecta: Hemiptera-Heteroptera: Gerromorpha + Nepomorpha). 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 91633 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1993) (AfrOBIS). 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 83 records from Planktic foraminifera abundance of Hole 14-135. 1 records from Planktic foraminifera abundance of Hole 8-72. 35548 records from Herpetology. 1608 records from Stable isotope analysis of benthic foraminifera and summer sea surface temperature reconstruction of sediment core PS2489-2. 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 257 records from Kernberge und Umgebung (Jena). 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 102 records from Muehlenbach bei Friesheim. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB6. 64 records from Occurrence of mammalia relicts at site Spitalhöhle. 6 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 26 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 63 records from Foraminifera abundance of Hole 59-450. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 480819 records from KTP Ring Data. 3471 records from Collection Foraminifera SMF. 98 records from Planktic foraminifera abundance of Hole 74-528. 2357 records from Foraminifera abundance of Hole 17-167. 163 records from Planktic foraminifera abundance of Hole 32-313. 37 records from Planktic foraminifera abundance of Hole 27-260. 59 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 197 records from Benthic foraminifera abundance of Hole 34-321. 109 records from Benthic foraminifera abundance of Hole 56-436. 154 records from Range table from benthic foraminifers in ODP Hole 174-1073A. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171A. 645 records from Phytoplankton abundance in surface water in March 1997, Ilo, Peru. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 18918 records from (Table 1) Distribution of benthic and planktonic foraminifers at DSDP Hole 28-270. 1 records from Microfossil abundance of Hole 35-323. 11 records from Subantarctic Fur sealsat Heard Island, 1987/88. 70 records from Exotic terrestrial flatworms, Macquarie Island. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 801904 records from Queensland Museum provider for OZCAM. 490 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 171B-1051A sediments. 1078 records from Fishes of the Congo River 2010 Expedition. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 54179 records from E. C. Smith Herbarium (ACAD). 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 776 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_98MC. 1 records from Collection Quaternary Small Mammals IQW. 121 records from Southern Giant Petrel census data within the Australian Antarctic Territory.. 33 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (2000m section). 281250 records from Quadrige. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 27299 records from NCSM Vertebrate Paleontology Collection. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 46528 records from Atlas of Danish Fishes. 6 records from Phytoplankton abundance in surface water in 2005, Ancon, Peru. 1576 records from MfN - Trace fossils. 487 records from Geometry of coccolith Coccolithus pelagicus in sediment core K708-007. 13230 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 233 records from Briòfits d'Andorra. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 194 records from (Table S2) Coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 15 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 1391 records from Open Mosaic Habitat Survey Group - Plants recorded during Open Mosaic Habitat survey in England and Wales (2012). 4153 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 598 records from (Table 5) Distribution of foraminifera in the Miocene section of ODP Hole 133-826A. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 42507 records from Bird Collection of Museum and Institute of Zoology PAS. 101480 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 1 records from Oribates humeralis. 4276 records from Coleção Entomológica Padre Jesus Santiago Moure-Trichoptera (DZUP-Trichoptera). 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 230 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 31 records from Description of Cathorops mapale, a new species of sea catfish (Siluriformes: Ariidae) from the Colombian Caribbean, based on morphological and mitochondrial evidence.. 169086 records from Estonian Nature Observations Database. 27264 records from Formidabel; Belgian Ants Database. 115 records from (Table 4) Relative abundances of benthic foraminifera in ODP Hole 128-799B. 7693 records from NHM, Heteroptera. 31273 records from SABCA. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 26 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD44. 71 records from Nannofossil abundance of Hole 64-478. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 51499 records from NRM-Fishes. 130 records from (Table 16) Calcareous nannofossil occurrences in ODP Hole 130-805B. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 8330 records from Nijmegen Natural History Museum (NL) - Herbarium. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 461 records from Guadeloupe_Bananier. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 71 records from Birdrace-do_elster_Dortmund. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 16 records from Two new emerald geometrid species of Telotheta Warren from Ecuador and Bolivia (Lepidoptera: Geometridae, Geometrinae, Lophochoristini). 51739 records from Crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34392 records from Water Beetles of Ireland. 85 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 455186 records from CAS Botany (BOT). 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 485 records from National Taiwan Ocean University. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 632 records from MVZ Hildebrand Collection (Arctos). 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 37664 records from H.A. Stephens Herbarium. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 94 records from Plasm bearing foraminifera counts of multinet M12/3_MSN557. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 44 records from Total foraminifera counts of multinet M21/5_MSN736. 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 119366 records from The digitization of plant specimens of NTU. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 41 records from Örtzemündung (Stedden). 86 records from Naturerlebnisraum Koppelsberg (Plön). 57 records from Schulgarten Fichteschule. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 44 records from Total foraminifera counts of multinet M27/2_MSN879. 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 79 records from Plasm bearing foraminifera counts of multinet M26/1_MSN844. 22853 records from Bryophyte herbarium, Oslo (O). 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_11-CTD132. 8 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 45 records from Nannofossil abundance of Hole 64-481A. 341 records from Size of planktic foraminifera at CTD station PS55/019. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 1 records from Microzooplankton abundance and biomass at station TT054_17-22. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD5. 22 records from Phytoplankton abundance at bottle station GOM1/6. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 11 records from Phytoplankton abundance at station Casma_2003-03-13_1, Casma, Peru. 11 records from Phytoplankton abundance at station Sechin_2003-11-06_2, Casma, Peru. 34 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 74 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/395-1. 10 records from Abundance of radiolaria at station UT99-5-1. 171 records from Sahrbachtal Kreis Ahrweiler. 49 records from Total foraminifera counts of multinet M42/3_MSN1367. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 32077 records from MfN - Fossil invertebrates Ia. 303 records from (Table 4) Distribution of sphenoliths at DSDP Site 82-563 in the North Atlantic. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 297 records from Planktic foraminifera counts of sediment core RC14-7. 1610 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1032 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 26515 records from Natal Museum - Mollusc Collection (AfrOBIS). 1824 records from CNAN/Scorpiones. 531 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 286 records from schulgarten. 137 records from Planktic foraminifera counts at CTD station PS55/019. 16 records from Dinoflagellate cysts of sediments core IOW211660-6. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_7-CTD82. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 75 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 34 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 292 records from (Table A1) Calcareous nannofossil of the Middle Cenomanian Event in ODP Site 207-1260. 19 records from Smear slide analysis on sediment core GeoB4214-1. 4 records from Nannofossil abundance of Hole 9-80A. 40 records from Nannofossil abundance of Hole 21-205. 46 records from Smear slide analysis on sediment core GeoB4216-1. 33 records from Coccolith counts of multinet SO119_MSN1272. 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 6321 records from Colección de Anélidos Poliquetos del Pacífico Mexicano (UANL). 14017 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 7 records from Nannofossil abundance of Hole 9-78. 4 records from Nannofossil abundance of Hole 60-454A. 3 records from Nannofossil abundance of Hole 51-417B. 27 records from Composition of the medium silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 647 records from Planktic foraminifera counts of sediment core V29-172. 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 1 records from Der Kreuzenzian und sein Bläuling. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 299 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE272. 56 records from Nannofossil abundance of Hole 82-558A. 49 records from Nannofossil abundance of Hole 80-548. 58 records from Planktic foraminifera counts of sediment core V28-122. 2025 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 3139 records from Foraminifera and stable isotopes of sediment core PS2076-3. 1403 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-205. 264 records from Planktic foraminifera counts of sediment core RC12-339. 3968 records from Antarctic Jellyfish. 21 records from Pollen data of trap CB2. 280 records from (Table 3) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-705A. 248 records from Orca observations from the shores of Macquarie Island. 3634 records from Herpetological collection of National Museum of Nature and Science. 376 records from Wupperaue bei Kemna (Wuppertal). 3290 records from (Figure 8) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 15-35. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 44 records from Distribution of late Neogene age calcareous nannofossils in ODP Hole 111-677A (Table 2). 3950 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 5918 records from Catálogo y recopilación de datos científicos de los lepidópteros nocturnos de México, pertenecientes a cinco familias. 51927 records from ANTARCTIC PLANT DATABASE. 156948 records from NBI. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 13461 records from Plant (JNHM-PL). 908 records from Spider (JNHM-SP). 24 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 27691 records from Collection Crustacea - ZMB. 436 records from Larval fish at Helgoland Roads in 2005. 16 records from Seawater carbonate chemistry and processes during experiments with benthic foraminifera Ammonia tepida. 896 records from (Table 4) Distribution of the large, few-chambered Globigerinelloides species in the Cismon core. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 2109 records from Helmintos de peces dulceacuícolas de México. 93 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 71 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832B. 2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 1230 records from Distribution of planktic foraminifera and calculated sea surface temperature of sediment core MSM05/5_712-1. 327 records from Elaboración de las fichas técnicas para la evaluación del riesgo de extinción de 18 especies de peces dulceacuícolas mexicanos. 1201 records from Computarización de las Colecciones de Anfibios y Reptiles del Centro de Investigaciones Biológicas de la Universidad Autónoma del Estado de Hidalgo. 466 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 1032 records from Flora y vegetación de la Sierra de San Carlos en el municipio de San Nicolás, Tamaulipas. 3954 records from Ibaraki Nature Museum, Fungi collection. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 287 records from Collection Odonata - SMF. 271 records from Collective List of Descriptions about Bacterial Isolates from Korea. 22042 records from SINBIOTA - marine data (OBIS South America, BRAZIL). 19063 records from Mammal specimens. 13438 records from Cameroon National Herbarium. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 980 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 1535 records from Mushroom Collection in BCRC. 272 records from Foraminifera distribution of sediment core LynchII-3. 4 records from Nannofossil abundance of Hole 3-16. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 72 records from (Table 3) Abundance of living foraminifers in bottom sediments from the Kandalaksha Bay. 2718899 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 25526 records from Marsh Monitoring Program - Amphibians. 37044 records from CIBIO, Alicante:ABH-GBIF. 87929 records from Herbario de la Universidad de Sevilla, SEV. 15709 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 71368 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1987) (AfrOBIS). 69009 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 13478 records from Herp Collection. 66 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-5. 5 records from Analyses of the recent components of sediment core PS1014-1. 452 records from Gelände des IVL (Zeckern). 177 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 3999 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 2243 records from Stable isotopes, diversity and composition of foraminifera in sediment core GeoB3004-1. 10 records from (Table A) Abundance of species detected in mussel beds within hydrothermal fields on the Mid-Atlantic Ridge. 31 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 5100 records from (Figure 2) Planktonic foraminifera abundance in DSDP Hole 93-603C. 16 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 2960 records from Herp specimens. 3 records from Analyses of the recent components of sediment core PS1403-1. 4044 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 1 records from Occurrence of mammalia relicts at site Warsaw. 12 records from Occurrence of mammalia relicts at site Kirkdale Cave. 3 records from Planktic foraminifera abundance of Hole 17-166. 83 records from Planktic foraminifera abundance of Hole 40-361. 650 records from Range table from planktonic foraminifers in ODP Hole 155-946A. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1222-1. 160 records from Duck sightings per month, Macquarie Island. 10 records from UC Davis Department of Anthropology Museum. 138 records from Planktic foraminifera abundance of Hole 26-250A. 691 records from Foraminifera abundance of Hole 24-236. 108 records from Planktic foraminifera abundance of Hole 94-611A. 152 records from Range table from planktonic foraminifers in ODP Hole 146-889A. 132 records from Range table from planktonic foraminifers in ODP Hole 177-1089A. 15555 records from Biological Records Centre - Coccinellidae Data. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 5759 records from EcoRecord - Mammal records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2577 records from Shellfish (WSHN-MS). 47 records from Antarctic Euphausiacea occurrence data from Norwegian Antarctic Research Expedition 1979. 1036 records from BUND - Dassower See (Lübeck/Dassow). 149 records from Biotop Binsenwiesen (Wehrheim/Taunus). 6 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 1 records from Occurrence of mammalia relicts at site Neasham. 147 records from Planktic foraminifera abundance of Hole 23-229. 85 records from Planktic foraminifera abundance of Hole 28-264A. 1012 records from Amphibian and Reptile Conservation - NARRS Data 2007 - 2011. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 539 records from (Table 1) Abundances of Discoaster species in ODP Hole 130-806C. 1 records from Range table from planktonic foraminifers in ODP Hole 139-856G. 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 66 records from Abundance of radiolaria in surface sediment, Sea of Okhotsk. 611 records from Planktic foraminifera abundance of Hole 94-608. 168 records from Range table from planktonic foraminifers in ODP Hole 155-942B. 102 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 81 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 3 records from Collection Aves fossil SMF. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 156 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4124 records from Herbario de la Universidad de La Laguna:TFC-Bry. 205 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 5 records from The tip of the iceberg: a distinctive new spotted-wing Megaselia species (Diptera: Phoridae) from a tropical cloud forest survey and a new, streamlined method for Megaselia descriptions. 540 records from (Figure 2a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3209. 127 records from Planktic foraminifera abundance of Hole 14-140. 1556 records from Planktic foraminifera abundance of Hole 7-64. 66 records from Foraminifera abundance of Hole 55-432A. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 182 records from Planktic foraminifera abundance of Hole 21-203. 1 records from Planktic foraminifera abundance of Hole 54-428. 525 records from Planktic foraminifera abundance of Hole 94-611C. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 1974 records from Range table from planktonic foraminifers in ODP Hole 160-967E. 233 records from Range table from planktonic foraminifers in ODP Hole 180-1115B. 3 records from Benthic foraminifera abundance of Hole 96-621. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 2294 records from Collection Echinodermata fossil SMF. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 760 records from Carabidae of Wales and England. 1740 records from Monitoring data from the federal state Berlin (Germany). 28222 records from Reptile Specimens. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 404 records from Range table from benthic foraminifers in ODP Hole 189-1171D. 38 records from Dinoflagellate abundance of Hole 71-512. 293 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 1924 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Donacobiidae. 31 records from Finnish Entomological Database: Blattodea. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 26990 records from British Lichen Society - BLS Rare and Threatened Lichen Records: England. 319 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 2 records from Pollen analysis of sediment profile GPL0 from Grosser Ploetzensee. 1160 records from Herbarium J Räsänen. 2193 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 1054 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 4591 records from WII Herbarium Dataset. 1 records from Oribates globulus. 2107 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 2412 records from Ohio University Invertebrate Paleontology Collection. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 44 records from "Schlechteberg" Ebersbach/Sa.. 1 records from Abundance of benthos infauna at station GIK23037-3. 175 records from PSUZC-Rodents Collection. 2443 records from Cnidaria MZS. 712 records from Herbier G. Garapin (BOUM). 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1911651 records from Consortium of California Herbaria. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 149 records from Total foraminifera counts from multinet M31/2_MSN888. 42788 records from Merseyside BioBank - North Merseyside Insects (unverified). 26936 records from The Brown University Foraminiferal Data Base (BFD). 822 records from Isotope tracer experiment: nematode abundance. 9552 records from Countryside Council for Wales - UK Biodiversity Action Plan Invertebrate Data for Wales. 7 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 7679 records from Herbier CNRST/INERA. 779 records from Guadeloupe_Ananas. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 1 records from Emesopsis infenestra Tatarnic, Wall & Cassis, 2011 (Heteroptera: Reduviidae), genus and species new to New Zealand. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 20891 records from Biological Records Centre - Brachycera (Diptera) records from Britain and Ireland to 1990. 850 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 151 records from Molluscan fauna of Gueishan Island of Taiwan. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 9123 records from Flora of Słowiński National Park, Poland. 11 records from Microzooplankton abundance and biomass at station TT045_11-2. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 36115 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 44 records from Wiesen am Treffpunkt Freizeit. 85 records from Ober-Olmer Wald. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 2233 records from Chrysomelidae of Poland. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 65535 records from OAC-BIO Herbarium. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 201522 records from CAS Ichthyology (ICH). 325 records from Triebesbach (Zeulenroda-Triebes). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 171 records from Total foraminifera counts of multinet M21/2_MSN652. 143 records from Planktic foraminifera counts at CTD station PS55/025. 7 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 4 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 43-384. 48 records from (Appendix 7) Pollen analysis of soil profiles obtained in the Nagqu area. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 78 records from Birdrace-Die_Laufenten-Braunschweig. 80 records from Landschaftsschutzgebiet Schmutterwald. 103 records from BIRDRACE federleser. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 107 records from Total foraminifera counts of multinet M26/1_MSN844. 20 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5115-1. 1297 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 2 records from Microzooplankton abundance and biomass at station TT050_11-4. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 2818 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 81 records from Birdrace-Die_Ornithomaten-Herford. 192 records from "Schwarzwassertal" bei Pobershau. 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 40 records from Total foraminifera counts of multinet M21/4_MSN716. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 35 records from Foraminifera species abundances from tow TT011_15-MOC78. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 72 records from Faunal assemblage of sediment core TR149-35. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 74 records from Total foraminifera counts of multinet M21/4_MSN699. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 3 records from Sarcodine counts and carbon biomass at station TT011_3-CTD33. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 4014 records from Herpetological specimens. 14 records from Nannofossil abundance of Hole 60-456. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 1508 records from Spider (YCEM-SP). 121 records from Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960. 2702 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 3 records from Pollen analysis of surface samples near sediment core Fiekers Busch. 1090 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 1 records from Microplankton counts and carbon biomass at station TT011_9-CTD115. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 11 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 4 records from Abundance of nematoda in sediment profile M3/1_031 from the Iberian deep sea basin (Table 5). 10 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_15-CTD152. 2 records from Nannofossil abundance of Hole 1-6A. 2 records from Nannofossil abundance of Hole 9-77A. 40 records from (Table 3) Distribution of calcareous nannofossils in DSDP Hole 92-598. 125 records from Range table from ostracoda in ODP Hole 143-866B. 1596 records from (Table 14) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-592. 7 records from (Table 5A) Neogene distribution of calcareous nannofossils at DSDP Hole 43-386. 57 records from Microzooplankton abundance measured on water bottle samples at station PS58/091-4. 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD45. 734 records from Mammals (NSMK-MM). 26491 records from Collection Vermes - ZMB. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE206. 5 records from (Table 7) Paleotemperature estimates for ODP Hole 104-642B. 3359 records from (Appendix) Relative abundance of planktonic foraminifera in ODP Site 138-846 late Quaternary sediments. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 34 records from Phytoplankton abundance at bottle station A8/2. 2 records from Nannofossil abundance of Hole 9-79A. 2 records from Nannofossil abundance of Hole 24-234. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 346 records from (Table C a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-23 at 3000 m water depth. 2599 records from Insecta ZMK. 154 records from (Table 10) Dinoflagellate cyst species distribution in ODP Hole 112-686B. 155 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2007. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 2000 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 144 records from Endocast Collection -CONICET- Argentina. 125 records from (Appendix) Benthic foraminiferal abundance at DSDP Hole 71-511. 6 records from Nannofossil abundance of Hole 10-91. 17 records from Coccoliths in sediment core PS1527-2. 6 records from Abundance of two benthic foraminifera species in sediment core 12930-007. 53514 records from Northern Territory Museum and Art Gallery provider for OZCAM. 235 records from PeECE III - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway, 2005. 500 records from Plant (KOBG_PL). 2077 records from Vascular plant specimens of Iida City Museum. 67112 records from Ehime University Coleoptera Collection. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 2440 records from Colección Nacional de Icnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 345 records from (Table T2) Biogenic and mineral composition of sediments cored in Vaale, Schleswig-Holstein. 49 records from NSG Hellbachtal. 14 records from Pollen profile Märchenwald A, Harz, Germany. 3166 records from WA. 2810 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 10607 records from Desmidiaceae Engels. 189 records from Fish larvae biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 66 records from Planktic foraminifera assemblage in sediment core GeoB1113-4. 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 2078 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 15 records from Occurrence of mammalia relicts at site Barrington. 15 records from Herdengelhoehle taxa and datings. 44 records from Planktic foraminifera abundance of Hole 19-188. 1497 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 1574 records from Lepidoptera - SNSD. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/554-2. 47 records from Pollen analysis of sediment core T89-16-PC. 2399 records from Estudio monográfico de la familia Rhamnaceae en México. 3253 records from Inventario florístico de la Sierra de Huautla, Morelos. 811 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 522 records from (UTCFM) University of Tennessee - Fossil Mammals Collection. 28647 records from IndOBIS, Indian Ocean Node of OBIS. 1185 records from (Appendix A) Foraminifera and stable carbon and oxygen isotope record of ODP Site 105-646. 62 records from (Table S1b) Measured tomographic parameters for Oridorsalis umbonatus during the PETM for ODP Site 208-1262. 32 records from (Table 1) Distribution of calcareous nannofossils in the Eocene of ODP Hole 113-689B. 246 records from Repatriación del material ictiológico de 12 estados de la República Mexicana, depositado en la colección ictiológica de la Universidad de Tulane, E.U.. 1522 records from Ibaraki Nature Museum, Fish collection. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 1248 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 43356 records from Canadian Museum of Nature Fish Collection. 81490 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1995) (AfrOBIS). 21680 records from Osaka Prefectural Minoh Park Insects Museum. 49354 records from SDNHM Birds Collection. 149 records from Benthic foraminiferal abundances from eight sites of the Northwest Australian shelf. 1657 records from Phragmites of Canada. 141104 records from Lichen Herbarium Berlin. 1020 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage (Australian Antarctic Data Centre). 7 records from Analyses of the recent components of sediment core PS1222-1. 5 records from Analyses of the recent components of sediment core PS1216-1. 152 records from AKG-Gelände (Bensheim). 1 records from On the Chilopoda from Turkey. 14 records from Occurrence of mammalia relicts at site Pavlov. 18 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 20 records from Range table from nannofossils in ODP Hole 199-1217B. 760 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_88MC. 890 records from Planktic foraminifera abundance of Hole 40-363. 33 records from Benthic foraminifera abundance of Hole 76-533A. 1257 records from Faun. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 994 records from Biological Records In Essex - Bat records for Essex from 1971 - present. . 101 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0028A. 3 records from Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia.. 195 records from Visual Plants (144.41.33.158) - Private collection of Eberhard Fischer. 468 records from Distribution of planktic foraminifera in surface sediment samples from cruise SO136. 6926 records from Distribution of planktic foraminifers of core V30-36. 159 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 29 records from (Table 2) Distribution of kummerform and sinistral specimens the planktic foraminifera Contusotruncana contusa in Cretaceous sediments. 244 records from Quarrendorfer Landschaftsschutzgebiet. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 28628 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 1182 records from Distribution of planktic foraminifera, factor analysis, SST of sediment core PS2498-1. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1016-1. 341 records from (Table A.06) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (125-250 µm). 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 41966 records from Tagged Seal Location Data from SOGLOBEC. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 498 records from Riedensee. 132 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 40 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 57 records from Occurrence of mammalia relicts at site Tornewton Cave. 13607 records from Fundación Miguel Lillo - Colección Ornitológica. 27 records from Occurrence of mammalia relicts at site Bettelküche. 105 records from Occurrence of mammalia relicts at site Sirgenstein. 1 records from Planktic foraminifera abundance of Hole 39-359. 167 records from (Table 6) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-601. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 7 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB4. 62 records from Occurrence of mammalia relicts at site Pestera Livadita. 44 records from Planktic foraminifera abundance of Hole 51-417A. 2083 records from Planktic foraminifera abundance of Hole 72-517. 102 records from Planktic foraminifera abundance of Hole 67-498A. 28 records from Hypostomus macushi, a new species of the Hypostomus cochliodon group (Siluriformes: Loricariidae) from Guyana.. 63 records from Range table from planktonic foraminifers in ODP Hole 167-1015A. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 44 records from Royal Horticultural Society - Pittosporum sucker (Trioza vitreoradiata) records acquired by the Royal Horticultural Society . 881 records from Range table from benthic foraminifers in ODP Hole 189-1170A. 33 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071F. 6 records from Oberservation of birds at station PS14/146 along 49° West. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 302 records from Kohlstattbrunnental. 191 records from Herbarium specimens of Bamboo collection Prafrance Générargue (BAMBO). 2 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 173-1069A. 1 records from Pelops ureaceus. 177 records from (Appendix) Ostracodes at DSDP Leg 72 Holes. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 165366 records from KUBI Mammalogy Collection. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 149 records from Naturnahes Tal in Siena. 20 records from Heteroptera - SMNG. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 2789 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 127 records from Birdrace_Schräge_Vögel-Herford. 53 records from Bad Bodenteicher Heide. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 179 records from Total foraminifera counts from multinet M31/3_MSN906. 171 records from Range table from benthic foraminifers in ODP Hole 171-1052E. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 10 records from Oberservation of birds at station PS14/157 along 49° West. 4579 records from Estacion Biologica Donana - CSIC, Anfibios (EBD_HERP). 13 records from Collection Reptilia fossil SMF. 4290 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 1 records from Conchological Society of Great Britain & Ireland - RISC Non-Native Species Records for Zebra Mussel. 593 records from Mamíferos voladores laguna El Tinije. 593 records from Amphibians and reptiles of Ireland. 57 records from A new Stomatorhinus (Osteoglossomorpha: Mormyridae) from the Ivindo River, Gabon, West Central Africa.. 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 47 records from Collection Pentastomida SMF. 1212 records from Birds fallen at Danish Lighthouses 1883 through 1939. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 272 records from Neuroptera (Insecta) of Ireland. 819 records from (Table T4) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P7-P8. 2467 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 4 records from Pachycondyla nigrita and related species in Southeast Asia.. 45809 records from Herpetology Collection - Royal Ontario Museum. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM6. 462 records from John Muir Trust - Knoydart Lichens, 1990. 375 records from Phthiraptera. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 413272 records from DATAVES. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 3942 records from UAFMC Mammals. 2571 records from RSPB - Black grouse surveys in Dumfries and Galloway 1980-2005 (RSPB and the Southern Uplands Partnership). 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 43 records from Notes on the snake eels of the genera Apterichtus and Ichthyapus (Anguilliformes: Ophichthidae) of the Central and South Pacific, with the description of a new species.. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 3061 records from Artròpodes d'Andorra. 105 records from Natural England - Species Surveillance Project - In-House Pilots records for 2012. 7509 records from Perot Museum of Nature and Science. 5 records from Arthropoden aus südostalpinen Höhlen.. 55839 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 3768 records from Eggs Specimen. 575081 records from Rio de Janeiro Botanical Garden Herbarium Collection. 11251 records from Herbarium areqvipense (HUSA). 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 4399 records from Fundacin Miguel Lillo - Coleccin Entomolgica. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 103 records from Birdrace-Die_Nachtigallen-Herford. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 103 records from BIRDRACE Die Otzberger. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 382 records from Reptilia ZMK. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 9 records from Willersalpe. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 57 records from Heidesee / Halle. 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 137 records from Abundance of planktic foraminifera at CTD station PS55/030. 2 records from Concentration of siliceous microplankton in surface sediments, brine. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC5. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 104520 records from Recent Invertebrates Specimens. 1808 records from Fongs d'Andorra. 100 records from Feriendorf Ober-Seemen. 4 records from Schulbiotop und Brigach (Villingen). 104 records from BIRDRACE Erlanger Piepmätzchen. 96 records from "Ahrschleife bei Altenahr". 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 127 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 8291 records from Ireland's BioBlitz 2012. 9 records from Phytoplankton abundance at station Sechin_2003-12-10_1, Casma, Peru. 4 records from Nannofossil abundance of Hole 4-29. 435 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 46 records from Hainbachtal in Oelsnitz/V.. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 320 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 39 records from (Table 1) Constituents of the sand-size fraction of ODP Hole 139-856A. 136 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1371. 36 records from Sedimentological investigation on core V15-168. 3 records from Sarcodine counts and carbon biomass at station TT007_3-CTD29. 118 records from Phytoplankton abundance at Station Sechin_EP2 in 2002, Casma, Peru. 1864 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 545 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 113 records from (Table 5) Ostracod assemblages of sediment core 9407. 66 records from Total foraminifera counts from M35/1_MSN1059. 49 records from Total foraminifera counts of multinet M10/2_MSN238. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/049-3. 21 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 668 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 63 records from Nannofossil abundance of Hole 7-62A. 9 records from Nannofossil abundance of Hole 26-255. 15 records from Description of lithologic section units of IODP Hole 325-M0036A. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 253 records from Mosquitoes (Diptera: Culicidae) of Ireland. 141 records from Total foraminifera counts of multinet M21/1_MSN614. 199 records from Planktic foraminifera counts at CTD station M39/4_357CTD-15. 137 records from Abundance of planktic foraminifera at CTD station M39/4_352CTD-11. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 6 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 32 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2157-3. 7 records from Abundance of radiolaria at station UT99-22-1. 8 records from Die Bachspezies 2008/2009. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 49 records from Plasm bearing foraminifera counts of multinet M26/1_MSN845. 94 records from Plasm bearing foraminifera counts of multinet M21/2_MSN647. 209 records from Palynomorpha in sediment core IK9373-10 from the Laptev Sea. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 9955 records from Benthic foraminifera abundance in counts of Hole PRAD1-2. 4 records from Distribution of meiobenthos in sediment core M19_216-2 of the northeastern Atlantic (Table 1). 42 records from Stadtwald Heide. 170 records from Nanoplankton abundance at station GeoB2021-1. 17266 records from Biological Records Centre - Caddisfly (Trichoptera) records from Britain and Ireland to 2003 . 724 records from Planktic foraminifera counts of sediment core V29-64. 9601 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 56 records from Nemertini - SMF. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 121 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 2 records from Nannofossil abundance of Hole 6-58. 665 records from Collection Echinodermata - ZMB. 2178 records from Palynological estimation of ODP Hole 189-1172A. 24 records from (Table 6) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-660A. 350 records from (Table 3b) Foraminiferal distribution chart of ODP Hole 122-761B. 2676 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 342 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 121 records from Birdrace_Deutschlands_enthusiast.Vogelkucker-Münster. 23048 records from Herpetology Collection. 279 records from Koleopterologen am Bausenberg. 212 records from Nanoplankton abundance at station GeoB2017-1. 57 records from Nannofossil abundance in sediment core PS1311-4. 2392 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 48 records from Pollen counts of sediment core GeoB9503-5. 3 records from Akita Prefectural Museum＋Sentipedes Specimens of Akita Prefectural Museum. 113941 records from Pacific Ocean Shelf Tracking (OBIS Canada). 191859 records from herbario. 2410 records from European Lepidoptera Observations by Donald Hobern. 22751 records from Lepidopteran specimens of Iwate Prefectural Museum. 407594 records from MAL. 131 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 19 records from Nannofossil abundance of Hole 31-298. 47 records from Nannofossil abundance of Hole 49-407. 553 records from Planktic foraminifera counts of sediment core V23-91. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 8 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE206. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 8089 records from Los díptera hematófagos y taxa relacionados de dos áreas protegidas del estado de Yucatán, México (Insecta). 6 records from Nannofossil abundance of Hole 7-63. 87 records from Nannofossil abundance of Hole 4-31. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 19 records from Exkursion in der Ehrbachklamm/ an den Erbach. 1808 records from Ant'Phipoda Database (New records). 2368 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 470 records from MfN - Isoptera Collection. 93 records from CCUG Microorganisms databases(Fungi). 202194 records from Tulane University Museum of Natural History. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 2008 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 3635 records from Raw counts of dinoflagellate cysts in several IODP and DSDP holes. 28 records from (Table 2) Distribution of late Eocene calcareous nannofossils in ODP Hole 149-897C. 1 records from Miriapodi di alcune grotte della Campania. 11926 records from Crispin S. Guppy Collection. 362 records from Northern Forestry Centre Arthropod Collection, Edmonton. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 1032 records from Percentages of planktonic foraminifera species in sediment core RC24-1. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 22 records from Occurrence of mammalia relicts at site Grabschütz. 165 records from (Table 1) Palynomorph concentrations in ODP Hole 105-646B samples. 15 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 17 records from (Table 2h) Nannofossil distribution chart of petroleum well Swan-3St. 11 records from Palynological investigation of profile Tso Kar. 140 records from Distribution of late Turronian planktonic foraminifers in ODP Hole 114-700B. 1 records from Akita Prefectural Museum＋Brachiopods Specimens of Akita Prefectural Museum. 61839 records from Herbarium Senckenbergianum (FR) - Fungi. 1594 records from BoGART. 4178 records from ARC- Plant Protection Research Institute, National Collection of Arachnida. 23146 records from BC Coastal Waterbird Survey. 3021 records from IBB bacterial database. 33944 records from Aranzadi Zientzi Elkartea. 377929 records from ``South Western Pacific Regional OBIS Data provider for the NIWA Marine Biodata Information System``. 13570 records from Royal Botanical Gardens Herbarium. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 30153 records from Kashihara City Museum of Insect. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Helmut Dalitz. 25793 records from NCOS1959_Crustacea (OBIS China). 9195 records from Shellfish Specimens of Miyazaki Prefecture Museum of Nature and History. 3787 records from Abundance of planktonic foraminifera in sediment core V12-122. 1435 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-345. 944 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 59406 records from PIROP (Shipboard Surveys). 106342 records from CSIRO Marine Data Warehouse (OBIS Australia). 12730 records from Banc de dades de biodiversitat de Catalunya-MolusCat. 11622 records from French Grapevine Genetic Resources Center. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 140 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 111 records from Planktic foraminifera abundance of Hole 9-79A. 166 records from Planktic foraminifera abundance of Hole 9-82A. 59 records from Planktic foraminifera abundance of Hole 28-266. 12 records from Foraminifera abundance of Hole 60-459. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 24 records from Range table from planktonic foraminifers in ODP Hole 146-889B. 182 records from Benthic foraminifera and algae abundance of Hole 81-554. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 62125 records from UCLA Donald R. Dickey Bird and Mammal Collection. 10 records from Sediment properties of core CD86_07_PC. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-112BX. 3 records from Analyses of the recent components of sediment core PS1010-1. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 3 records from Casuarinicola australis Taylor, 2010 (Hemiptera: Triozidae), newly recorded from New Zealand. 410 records from Planktic foraminifera distribution of sediment core 75KS5. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 235 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 20 records from Occurrence of mammalia relicts at site Picken´s Hole. 42 records from Foraminifera abundance of Hole 24-236. 172 records from Foraminifera abundance of Hole 59-448A. 1347 records from (Table 16A) Occurrences of planktonic foraminifers in DSDP Hole 90-594, samples 594-1-CC through 594-30-CC. 50 records from Planktic foraminifera abundance of Hole 11-106. 774 records from Planktic foraminifera abundance of Hole 80-549A. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 742 records from (Appendix A) Relative abundances of smaller size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 294 records from Naturgarten Langenholtensen. 20 records from Occurrence of mammalia relicts at site Kesslerloch. 10 records from Occurrence of mammalia relicts at site Aveley. 118 records from Planktic foraminifera abundance of Hole 17-165A. 4 records from Planktic foraminifera abundance of Hole 23-223. 39 records from Planktic foraminifera abundance of Hole 28-265. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D4. 201 records from Planktic foraminifera abundance of Hole 11-103. 1592 records from Range table from planktonic foraminifers in ODP Hole 139-856A. 96 records from Range table from planktonic foraminifers in ODP Hole 145-883B. 78 records from Range table from planktonic foraminifers in ODP Hole 169-1035E. 14 records from Benthic foraminifera abundance of Hole 96-620. 9 records from Occurrence of mammalia relicts at site Siebenlinden 1. 197469 records from UMMZ Herpetology Collection. 813 records from Foraminifera abundance of Hole 64-479. 354 records from Microfossil abundance of Hole 35-323. 176 records from Planktic foraminifera abundance of Hole 62-463. 366 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 12 records from Range table from planktonic foraminifers in ODP Hole 182-1133A. 258 records from Range table from benthic foraminifers in ODP Hole 144-877A. 142 records from (Table 3) Distribution of benthic foraminifers in middle Miocene sediments of ODP Hole 182-1134A in the Great Australian Bight. 2980292 records from DOF. 290333 records from AMNH Mammal Collections. 2 records from Abundance of benthos infauna at station GIK23043-2. 6 records from Taxonomic notes and distribution extension of Durga Das’s leaf-nosed bat Hipposideros durgadasi Khajuria, 1970 (Chiroptera: Hipposideridae) from south India. 337366 records from British Lichen Society - BLS Lichen Database: England. 13 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 496 records from Range table from benthic foraminifers in ODP Hole 145-887A. 666 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-908A. 1 records from Results of palynological analysis of Hole 302-M0001A. 64 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 1 records from Nothrus bicolor. 65 records from EcoRecord - Alderfly (Megaloptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 40 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Apodidae. 193 records from The velvet spiders: an atlas of the Eresidae (Arachnida, Araneae). 1 records from On centipedes (Chilopoda) of Albania, 2. 83 records from Range table from planktonic foraminifers in ODP Hole 139-858A. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 40 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1072A. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 2618 records from MEXU/Agavaceae. 1942 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 117153 records from National vegetation diversity inventory and mapping plan. 14 records from Range table from planktonic foraminifers in ODP Hole 182-1129B. 116 records from Range table from benthic foraminifers in ODP Hole 198-1213B. 374 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_91MC. 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 53403 records from Collection Arachnology SMF. 751 records from (Table T5) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1212B, Shatsky Rise, Pacific Ocean. 2005 records from EcoRecord - Odonata (Dragonfly and Damselfly) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 184611 records from The Flora of County Waterford. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 326 records from Colección nacional de palmas de Colombia - JBQ. 228 records from Phytoplankton abundance in surface water in September 1996, Paita, Peru. 11 records from Oberservation of birds at station PS14/145 along 49° West. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 47672 records from Birds (KIDR-BI). 1188 records from Countryside Council for Wales - Squirrel Collation for Wales. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 111991 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 29441 records from Animal Sound Archive. 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 403738 records from Marine Conservation Society - Seasearch Marine Surveys . 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 7626 records from Naturhistorisches Museum Mainz, Herbarium von Ruprecht Düll. 41 records from Scottish Natural Heritage - Site Condition Monitoring of Annex II Vertigo species in Scotland. 46710 records from Invertebrates of the Gothenburg Natural History Museum (GNM). 5406 records from Colección de Mastozoología. 505723 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 6776 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Diptera Records up to Dec 2011. 1998 records from Aves de la cuenca media del río Bogotá. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 1733 records from Birds collection of Abiko City Museum of Birds. 9136 records from “Endemic Species Research Institute Moth Survey” Dataset. 1 records from Oppia glaucina. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 2015 records from (Appendix B) Benthic foraminifera extinction group species in combined DSDP Hole 33-317B and sediment core KR9912-PC4. 926 records from Coleoptera types of John Sahlberg. 6062 records from Lichens of Knyszyn Forest. 3 records from Arthropoden aus südostalpinen Höhlen.. 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 36 records from Norwich Reptile Study Group - Norwich Reptile Study Group Records for 2010. 1440 records from Museum TwentseWelle (NL) - Fossil Collection. 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 17129 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 650 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anatidae. 9 records from Austrolebias univentripinnis sp. nov. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the Mirim Lagoon basin, southern Brazil.. 27753 records from Fungi collection of the University of Eastern Finland. 1 records from Oribates coracinus. 360 records from (Figure 1c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3192. 99 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 2546 records from The atlas of butterflies in Kraków. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 111 records from Birdrace-Uhulogen-Lippe. 74 records from (Table 7) Miocene to Pliocene nannofossil range chart for ODP Hole 134-832B. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 1415 records from Plant observations from Białowieża National Park. 71 records from Bolzplatz. 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1045. 13 records from Benthic macrofauna abundance of sediment core 12930-073. 581 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 196 records from (Figure 4) Distribution of dinoflagellates in ODP Hole 129-802A. 43443 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 6855 records from Echinoderm collection of National Museum of Nature and Science. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 859 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 555 records from FFH-Gebiet "Calwer Heckengäu". 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD61. 12 records from Phytoplankton abundance in surface water in 1993, Ancon, Peru. 3580 records from Royal Ontario Museum - Entomology (ROME). 40 records from Coccolith counts of multinet M32/5_MSN990. 51 records from Nannofossil abundance of Hole 20-200. 126 records from Nannofossil abundance of Hole 39-357. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 10317 records from KUBI Ichthyology Tissue Collection. 85 records from Insektenvielfalt Ahe/Weichelsee. 51 records from Steinbachtal (Würzburg). 51 records from Schrebergarten Düsseldorf Oberkassel. 23 records from Ackerrain Plönhagen. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 11 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 43 records from Diatom assamblage in samples from sediment trap NB6. 11 records from Microzooplankton abundance and biomass at station TT050_21-13. 1 records from Microplankton counts and carbon biomass at station TT007_3-CTD29. 26 records from Coccolith counts of multinet M32/5_MSN988. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 22 records from Heilpflanzen im Hainbachtal. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 39 records from Soolbach-Tal. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 94 records from Landschaftsschutzgebiet Buchhorst 4. 369 records from BIRDRACE Havelland. 114 records from BIRDRACE LiLaLau. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 185 records from Total foraminifera counts of multinet M21/1_MSN606. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 148 records from Total foraminifera counts of multinet M21/2_MSN643. 749 records from Total foraminifera counts from multinet M32/5_MSN979. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 39 records from ECOCEAN MantaMatcher. 65842 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 100 records from BIRDRACE Stuttgart 100 trööt. 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 13 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 222 records from Total foraminifera counts from multinet M31/3_MSN910. 151 records from (Appendix A) Abundance of calcareous dinoflagellates of sediment core GeoB2204-2. 1850 records from (Appendix 2) Abundances of benthic forminifera in ODP Hole 113-690B. 110 records from Birdrace-LiLaMai-Vechta. 131 records from Total foraminifera counts of multinet PO247/2_MSN1377. 19042 records from Natural History Museum Rotterdam (NL) - Chordata collection. 4 records from Bayerische Donau - Etterzhausen. 2792 records from Birds (UWEP-BI). 325 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE258. 255 records from (Table 3) Occurrences of ostracodes in ODP Hole 122-763B. 122 records from Planktic foraminifera counts at CTD station PS55/043. 42 records from Collection Aves - PUM. 7 records from Nannofossil abundance of Hole 9-82. 352 records from Ostracoda abundance of Hole 95-612. 72 records from Nannofossil abundance of Hole 31-292. 70 records from Nannofossil abundance of Hole 67-497. 16 records from Nannofossil abundance of Hole 24-235. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 1361 records from Collection Arachnida - SNSD. 3956 records from Royal Saskatchewan Museum Collection. 556 records from Distribution of planktic foraminifers of sediment core D117. 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 85 records from Unterbrucker Weiher. 88 records from Teich Berlin Wuhlheide. 134 records from Birdrace-Raumpatrouille_Oriolus-Münster. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_26-4. 3 records from Sarcodine counts and carbon biomass at station TT007_4-CTD39. 6 records from Microzooplankton abundance and biomass at station NBP97-03-06-8. 179 records from Platyhelminth collection of National Museum of Nature and Science. 17 records from Phytoplankton abundance at station Rigel_2_2005-02 in Febraury 2005, Chipana, Chile. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/043-2. 401 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1768-8. 7 records from Distribution of meiobenthos in sediment core M23_133 of the northeastern Atlantic (Table 1). 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 68 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 128 records from Nannofossil abundance of Hole 4-25. 4 records from Nannofossil abundance of Hole 85-574. 1393 records from Rancho Grande. 65 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 191817 records from The Distribution Atlas of Butterflies in Poland. 52 records from Benthic foraminifera and phytodetritus species in sediments from DSDP Site 85-574. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 3415 records from Plant Specimens collections of the Kyushu UNniversity Museum. 34 records from annex4. 7 records from Nannofossil abundance of Hole 7-63A. 7 records from Nannofossil abundance of Hole 38-336. 36 records from Nannofossil abundance of Hole 14-141. 49339 records from Environment Agency - Environment Agency Non-native Species records v1. 1728 records from Saproxylic Beetles of the Tatra Mts.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 909 records from South American Antarctic Marine Biodiversity Literature. 576 records from National Collection of Yeast Cultures,Norwich,UK. 1 records from Zetes gilvulus. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 2073 records from Bryophyte collection of Jyväskylä University Museum. 2343 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 195 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 431 records from Ictiofauna del sistema lagunar costero Chacahua-La Pastoría, Oaxaca. 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 159 records from (Table 1) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-747. 940 records from (Table 10) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 24-238. 464 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 5 records from Loricifera - SMF. 481 records from (Table 3f) Foraminiferal distribution chart of petroleum well Montara-2. 854 records from Collection Hunsrückschiefer - SMF. 478 records from EASIANET. 7490 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Trawl. 37240 records from LSUMZ Mammals Collection. 519781 records from Danish Mycological Society, fungal records database. 5 records from Regenwasserabfangbecken Erlenbach. 28 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Pycnogonida.. 86 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 348 records from (Table 2) Distribution of planktonic foraminifera in ODP Hole 183-1136A. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 323 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 310 records from (Table 2) Distribution of main species of planktonic foraminifers in Core AMK21-2179, Woodlark Basin. 282 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 91 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-765C. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 8 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE262. 138 records from Pollen profile from Wurzacher Becken. 333 records from Revisión del género Zabrotes para México (Coleoptera: Bruchidae). 44 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 5298 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 31 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part II. 352 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 35 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 116417 records from Michigan State University Herbarium Lichens. 13708 records from Bohart Museum of Entomology, UCD. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 491 records from (Table 1) Relative abundances of planktic foraminifers in bottom sediments from Core AMK4-316GC. 24 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 1170 records from Colección de Cnidarios. 277 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 12963 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 289 records from Summary of ecologically and stratigraphically important foraminifera in surface samples of the NW African continental margin (Table 3). 325 records from (Table A.07) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (150-500 µm). 626 records from (Table 2) Benthic foraminifera distribution in sediment core ASV11-880-3. 16 records from Tettigettalna josei (Boulard, 1982) (Hemiptera: Cicadoidea): first record in Spain, with notes on the distribution, genetic variation and behaviour of the species. 127 records from Industriegebiet (Kempen). 115 records from Wismar Bucht coast-watching. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 2 records from Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae).. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 21 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB07 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MAY-1995-D2. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 14 records from Planktic foraminifera abundance of Hole 20-199. 16 records from Nannofossil abundance of Hole 24-236. 1167 records from Macroinvertebrate Data BOKU. 82 records from Planktic foraminifera abundance of Hole 14-144A. 71 records from Planktic foraminifera abundance of Hole 15-153. 151 records from Planktic foraminifera abundance of Hole 11-104. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 182 records from Relative abundance of live benthic foraminifera of sediment core M5/2_88MC. 685 records from Ostracode relative abundances and geochemistry in surface sediments from Lake Ohrid. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 3477 records from Aves laguna El Tinije. 870 records from Percentages of planktonic foraminifera species in sediment core V22-38. 551 records from Foraminifera abundance of sediment core CS73-34. 187 records from (Table Ib) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 74-528 on the Walvish Ridge, South Atlantic. 918 records from Invertebrate survey, Heard Island 2001. 2 records from Radiolaria assemblage in sediment core GIK23400-3. 48 records from Planktic foraminifera abundance of Hole 47-397. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 26 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 286 records from Occurrence of mammalia relicts at site Roc de Combe. 576 records from Planktic foraminifera abundance of Hole 23-229A. 48 records from Planktic foraminifera abundance of Hole 6-47. 167 records from Planktic foraminifera abundance of Hole 15-151. 104 records from Planktic foraminifera abundance of Hole 28-265. 798 records from Planktic foraminifera abundance of Hole 27-262. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 604 records from (Table 7) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583G. 35 records from Planktic foraminifera abundance of Hole 67-499A. 18 records from Range table from planktonic foraminifers in ODP Hole 175-1080A. 110 records from Range table from planktonic foraminifers in ODP Hole 182-1132C. 675 records from Benthic foraminifera and algae abundance of Hole 81-553A. 14 records from Microfossil abundance of Hole 29-277. 107485 records from Botany Division, Yale Peabody Museum. 15 records from Pollen analysis of sediment profile MU1 from Muggesfelder See. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 140 records from Range table from planktonic foraminifers in ODP Hole 182-1129D. 60 records from Range table from benthic foraminifers in ODP Hole 139-858C. 56 records from Range table from benthic foraminifers in ODP Hole 144-874A. 4 records from Dinoflagellate abundance of Hole 81-554A. 1 records from Pollen and spore abundance of Hole 42-379A. 13596 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 59 records from Main components of radiolarian assemblage at Site 177-1092. 49 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1008. 2253 records from Irish National Crayfish Database. 32 records from Revision of the genus Sinopoda Jäger, 1999 in Laos with discovery of the first eyeless huntsman spider species (Sparassidae: Heteropodinae). 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 7830 records from Mollusca Collection. 807 records from (Table 4) Planktonic foraminifer abundance of ODP Hole 162-981A. 72 records from Range table from planktonic foraminifers in ODP Hole 172-1058A. 59 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 564 records from Central Scotland Forest Trust - Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 2 records from Benthic foraminifera abundance of Hole 42-374. 56 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 5 records from Microfossil abundance of Hole 50-416A. 72 records from Ostfriesland. 66 records from Klostergarten St Luzen. 31930 records from Insect specimens database of Shizuoka Prefecture Museum of Natural History. 159 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 57 records from Range table from benthic foraminifers in ODP Hole 159-960C. 18 records from Range table from benthic foraminifers in ODP Hole 144-871B. 230 records from Range table from benthic foraminifera in ODP Hole 199-1220B. 9 records from (Tab. 9) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 36-330, Falcland Plateau. 18000 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 430 records from Collection Strepsiptera SMF. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 1036 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zone P4. 1101354 records from Botany (UPS). 12555 records from Natural History Museum Rotterdam (NL) - Plantae collection. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 31020 records from National Museum of Natural Science. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 43 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1017. 89 records from Dixidae (Diptera) of Ireland. 25 records from Hemiodus jatuarana, a new species of Hemiodontidae from the rio Trombetas, Amazon Basin, Brazil (Teleostei, Characiformes).. 1 records from First record of Eggplant Mealybug, Coccidohystrix insolita (Hemiptera: Pseudococcidae), on Guam: Potentially a major pest. 540 records from (Table 1) Pleistocene planktonic foraminiferal assemblages at ODP Site 128-798. 3695 records from Distribution of planktic foraminifera in ODP Site 202-1240 samples. 1794 records from Herbarium BSG Lichenes. 242082 records from Carnet en Ligne. 32 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2002. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 4 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 266 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 54 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 2312 records from Mycological collection of the National Museum. 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 253095 records from Lyman Entomological Museum (LEMQ). 711 records from Odonata collection, NTNU, Trondheim. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 17 records from (Table 4) Total phytoplankton biomass, biomass of certain algal groups in the upper mixed layer and the water column, and contribution of the algal groups to total biomass of phytoplankton in the southwest Kara Sea on August 9-12, 2007. 3 records from Hornmilben (Oribatida) [pages 213 to 260]. 11 records from (Tables S1,2) Stable isotopes in muscle tissue of polar bears (Ursus maritimus) from various regions of the Arctic. 16102 records from EcoRecord - Diptera Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 447 records from Orthoptera del Museo de Entomología de la Universidad del Valle. 42488 records from NCSM Herpetology Collection. 200579 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): 1999 Atlas Dataset for Great Britain and Ireland. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 4579 records from Herbarium WRSL, Flora of the Silesia. 2753 records from (Figure 8 a) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-535. 25486 records from Biological Records Centre - Opiliones (Harvestman) Dataset. 85250 records from Green Plant Herbarium (TRT). 27 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 4567 records from Herbarium WRSL, Main Collection. 11004 records from Dataset of Phenology of flora of mediterranean high-mountains meadows (Sierra Nevada). 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 51148 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 30327 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 491 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 238 records from Revision der europäischen Gattungen und Arten der Familie Brachychthoniidae (Acari, Oribatei) Teil 1. Allgemeiner Teil: Brachychthoniidae Thor, 1934. Spezieller Teil: Liochthonius v. d. Hammen, 1959, Verachthonius nov. gen. und Paraliochthonius nov. gen.. 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 8 records from Order Diptera, family Mydidae. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Miriapodi di alcune grotte della Campania. 6997 records from CHAS Vertebrates. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 1 records from Zetes morticinus. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 60 records from NABUGEO1. 3 records from Blankenfelder See. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 9997 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 1119094 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 97 records from Döchtbühlwald (Bad Waldsee). 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB3708-1. 34 records from Total foraminifera counts of multinet M21/4_MSN722. 9 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 18004 records from Census of the animals of Benin. 64 records from Issumer Fleuth. 248 records from Schulgarten der Volksschule. 1984 records from Planktic foraminiferal species counts in GeoB1117-2. 45 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 10 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 80889 records from Scottish Natural Heritage - Standing Waters Database. 6 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 59 records from Schriesheimer Steinbruch. 193 records from Geometry of coccolith Coccolithus pelagicus in sediment core GIK23065-3. 27 records from Ostracoda abundance of Hole 42-376. 76 records from Birdrace-Birding_for_Nature-Bonn. 124 records from Wiesenbiotop am Wasserturm. 117 records from Naturschutzgebiet Kochertgraben. 721 records from IBF Monitoring of Plant Galls. 2 records from Hildener Heide - Spörkelnbruch (Haan). 315 records from Size of planktic foraminifera at CTD station PS55/030. 328 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 486 records from Dinoflagellates of sediment core GeoB1523-1. 75 records from Abundance of microzooplankton measured on water bottle samples during POLARSTERN cruise ANT-X/6. 35 records from Phytoplankton abundance at bottle station A3/66A. 234 records from Clyde River Foundation - Allis Shad (Alosa alosa) distribution for Scotland, historical to present. 78 records from Aktion - Friedensburg Oberschule. 5 records from Nannofossil abundance of Hole 34-320A. 2 records from Nannofossil abundance of Hole 9-82A. 64 records from Nannofossil abundance of Hole 24-231. 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 206 records from Total foraminifera counts from multinet M31/3_MSN908. 68 records from Plasm bearing foraminifera counts from multinet M32/3_MSN956. 109 records from Phytoplankton abundance at station CD46_1305C#2. 1575 records from Porifera MZS. 16 records from Phytoplankton abundance at station Casma_2003-03-27_1, Casma, Peru. 47 records from Nannofossil abundance of Hole 64-479. 4 records from Nannofossil abundance of Hole 4-31. 120 records from Nannofossil abundance of Hole 47-397. 2 records from Nannofossil abundance of Hole 20-199. 5 records from Nannofossil abundance of Hole 74-529. 6 records from Nannofossil abundance of Hole 55-430B. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 52 records from Total foraminifera counts of multinet M21/4_MSN713. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 133 records from Total foraminifera counts of multinet PO247/2_MSN1379. 175 records from Planktic foraminifera counts at CTD station M39/4_361CTD-18. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 1371 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 197 records from Coleoptera identified from the Horton Kirby site, near London. 111 records from Planktic foraminifera counts at CTD station PS55/037. 1 records from Microzooplankton abundance and biomass at station TT050_2-10. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-04-1. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 1 records from Phytoplankton abundance at station Rigel_3_2005-08 in August 2005, Chipana, Chile. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 136 records from (Table 7) Ostracod assemblages of sediment core 9408. 12 records from Nannofossil abundance of Hole 20-200. 12 records from Ostracoda abundance of Hole 32-306. 67 records from Relative abundance of coccosphere-units of sediment core GIK23071-2. 23 records from Coccolith counts of multinet SO119_MSN1303. 2 records from Nannofossil abundance of Hole 1-5. 965 records from Northumberland Wildlife Trust - Squirrel Records for 2002 - 2005. 5 records from Nannofossil abundance of Hole 29-280. 6 records from Nannofossil abundance of Hole 60-457. 109 records from Broadland Environmental Services Limited - Reptile distribution along the River Bure, Broadland (2010) . 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/061-3. 279 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 27 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 86 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 88 records from Nannofossil abundance of Hole 40-362. 10 records from Ostracoda abundance of Hole 44-390. 467 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Site 202-1237. 832 records from (Appendix 2) DSDP Site 94-610 ostracode species census data. 2803 records from IMEDEA-INSECTA. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 3362 records from Coimbra Collection of Algae. 94 records from Collection Bryozoa - ZMB. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 206 records from Folklore and Natural History Museum Amphibia. 197 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 945 records from (Appendix D) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748C. 4825 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1 records from On the Chilopoda from Turkey. 3 records from Antarctic Arrow worms. 375 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 105-646A. 1042 records from (Table 1) Relative abundances of Maastrichtian benthic foraminifera at El Kef, Part I. 2444 records from (Table 12A) Occurrences of planktonic foraminifers in selected samples of DSDP Holes 90-590 and 90-590A. 260 records from Range table from ostracoda in ODP Hole 144-873B. 23 records from Meiofauna abundance in sediment core 12930-075. 175 records from (Table 3) Benthic foraminifers in the surface sediment layer of the southern Laptev Sea. 9067 records from Atlas Nacional de Anélidos Poliquetos de México (ICMyL-DF, UNAM). 357 records from (Appendix D) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in ODP Site 146-893. 33 records from (Appendix 2) Abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core SU81-18. 11737 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 1 records from Murcia rubra. 23 records from Palynology of profile Füramoos III. 8072 records from Riqueza específica, distribución y abundancia de aves acuáticas en la ensenada de La Paz, Baja California Sur, México. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 726 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-077. 6909 records from Herbario del Departamento de Biología Vegetal (Botánica) de la Universidad de La Laguna, Tenerife (TFC). 1309 records from Mongolian Plant (MMNH-PL). 104 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE241. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 4417 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 403 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 26 records from Marine Invertebrate Diversity Initiative (OBIS Canada). 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 36 records from Pollen profile ADR309. 816 records from Peces de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 55 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV8. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 19614 records from Mammal specimens. 68081 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 58 records from CNIN/Tipos Diptera. 317 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-714A. 29 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 23601 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 1 records from Akita Prefectural Museum＋Specimens of Phylum Nemertea of Akita Prefectural Museum. 576 records from (Table 16) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-710A. 46022 records from West African Vegetation Database. 650 records from Relative abundance of planktic foraminifera in sediment core K708-001. 17 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM8. 840 records from (Table T2) Planktonic foraminiferal stratigraphy of ODP Hole 173-1067A sediments. 197 records from Reconstruction of surface water temperature of sediment core GIK12310-4, Cape Barbas, North-West Africa (Appendix Tab. 3). 62592 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1997) (AfrOBIS). 16600 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 495 records from Life Science National Tsing Hua University. 1684 records from MfN Fish Collection, Zoology. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 1978 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-339. 716 records from Foraminifera distribution of sediment core Chain61-19. 417 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 1 records from Arthropoden aus südostalpinen Höhlen.. 582 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean. 275 records from Wald und Wiese am Buchwald. 410 records from Gemeindegebiet Weikendorf (Marchfeld). 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 3 records from Occurrence of mammalia relicts at site Igstadt I. 4 records from Occurrence of mammalia relicts at site Ceremosnica. 5 records from Occurrence of mammalia relicts at site Valea Sesii Cave. 278 records from Planktic foraminifera abundance of Hole 39-354. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 12 records from Range table from benthic foraminifers in ODP Hole 181-1120B. 90105 records from Paleobotany Division, Yale Peabody Museum. 1 records from Nothrus minimus. 2430 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 415 records from Planktic foraminifera abundance of Hole 29-281. 329 records from Planktic foraminifera abundance of Hole 60-458. 166 records from Foraminifera abundance of Hole 22-213. 279 records from Planktic foraminifera abundance of Hole 11-98. 3 records from Range table from planktonic foraminifers in ODP Hole 139-856E. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1686 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 4842 records from (Table 6) Planktonic foraminifer abundance of ODP Hole 162-982B. 285 records from (Table 4) Planktic foraminiferal abundance in Oligocene to Early Miocene sediments of ODP Hole 177-1090E on the Agulhas Ridge, South Atlantic. 15975 records from condoncollection. 775 records from Insect (GNHM-IN). 95 records from Überschwemmungsgebiet der Wied. 199 records from Halberg bei Neumorschen. 622 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 20 records from Occurrence of mammalia relicts at site Stellmoor. 8 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 53 records from Planktic foraminifera abundance of Hole 29-278. 186 records from Planktic foraminifera abundance of Hole 94-610. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 5173 records from Planktic foraminifera abundance of Hole 15-147. 11 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 6 records from Range table from planktonic foraminifers in ODP Hole 151-912B. 1 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071B. 330 records from Phytoplankton abundance in surface water in February 1998, Pisco, Peru. 8974 records from NCSU_Darwincore. 74734 records from Herbarium Senckenbergianum (FR). 3 records from Nouvelles fourmis de Madagascar.. 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 14549 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 253 records from Planktic foraminifera abundance of Hole 24-233. 6693 records from National System of Protected Areas in Poland - Animals. 468 records from Collection Diptera - SMF. 3709 records from Naturalis National Natural History Museum (NL) – Cnidaria and Porifera fossils. 290 records from The symphytognathoid spiders of the Gaoligongshan, Yunnan, China (Araneae: Araneoidea): Systematics and diversity of micro-orbweavers. 995 records from Palynological analysis of sediment core GeoB9508-5. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 146 records from BIRDRACE VdW Wilder Westen. 25 records from Distribution of planktic foraminifera of sediment core GIK23359-4 at stadium 5.5. 36351 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 91 records from Benthic foraminifera abundance of Hole 84-569A. 43 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 2 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071A. 56685 records from MISS_DC_01MAR2006. 13646 records from Senckenberg - CeDAMar Resource. 12147 records from Danish Ants (Formicidae). 3 records from Australian Formicidae.. 28648 records from The DNA and Sample Repository at AIT. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 259408 records from MSB Mammal Collection (Arctos). 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Heliornithidae. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 55816 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 49637 records from Monitoring data from the federal state Hesse (Germany). 783 records from (Figure 2) Benthic foraminifera abundance of DSDP Hole 93-603C. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 1 records from Benthic foraminifera abundance of Hole 96-624. 140 records from Range table from benthic foraminifers in ODP Hole 139-857C. 208 records from Dinoflagellate cysts of ODP Hole 189-1171D. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 44 records from Flora und Fauna in unserer Kita. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 1657 records from Reptiles, Amphibians and Fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 2046 records from (Table T3) Benthic foraminfera stratigraphy of ODP Hole 199-1221C sediments. 538350 records from iNaturalist research-grade observations. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 191 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s. l., Scelioninae). 16 records from Inventario de Murciélagos Floreña I, Yopal, Casanare. 1932 records from (Table 6) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-852B. 106941 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 31 records from Siphonaptera. 99300 records from Landesmuseum Kärnten. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 6943 records from DMNS Egg Collection (Arctos). 66 records from The Neotropical annual killifish genus Pterolebias Garman (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology, and taxonomic revision.. 7 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 1373 records from (Supplementary data 1) Count data of the observed dinoflagellate cyst species from sediment core GeoB10709-5. 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Conopophagidae. 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 44561 records from Flora of the Stołowe Mts.. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 12 records from Clarias insolitus, a new species of clariid catfish (Teleostei: Siluriformes) from southern Borneo.. 1210 records from NPWS Seal Database. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 57879 records from Albany Museum Grant. 21704 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 1476 records from Harvestmen_of_French_Guiana. 29087 records from Naturalis Biodiversity Center (NL) - Collembola. 93 records from Haarbach Höfe. 203945 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 2 records from A new trapdoor spider species from the southern Coast Ranges of California (Mygalomorphae, Antrodiaetidae, Aliatypus coylei, sp. nov,), including consideration of mitochondrial phylogeographic structuring. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 1 records from Contributions a la faune Myriapodologiwue Mediterraneenne. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 1 records from Myriopoden von Epirus. 58 records from Mamíferos laguna El Tinije. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 115 records from Total foraminifera counts of multinet M33/1_MSN1028. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 1 records from Murcia trimaculata. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 1914 records from Macrophytes_CLF. 2413 records from Literature based species occurrence data of birds of North-East India. 37 records from Berlin - Treptower Park / Karpfenteich. 1900 records from Fungi Collection. 850 records from Shellfish (NHMK-MS). 101 records from Naturgrundstück (Eutin). 5 records from Streuobstwiese (Mittelgasse 4). 99 records from Dorfrand Mauderode. 65 records from LSG "Großes Bruch". 6 records from Sächsische Schweiz (Pfaffenstein). 1 records from Karpfenteich, Klasse 6d. 116 records from Sürther Aue. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 157 records from Total foraminifera counts from M35/1_MSN1069. 69 records from "Schwarzes Teich" (Waldpark Radebeul). 155 records from Bammentaler Duft- und Heilkräutergarten. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 258 records from BIRDRACE Raumpatrouille Oriolus. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 110 records from BIRDRACE Angeliter Ornis. 107 records from BIRDRACE Borussia Zippammer. 62 records from Lebensraum Dorf. 53 records from BIRDRACE Taubenhaucher. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 145 records from Total foraminifera counts from multinet M32/3_MSN957. 111 records from Total foraminifera counts of multinet M10/2_MSN219. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 97 records from Total foraminifera counts from M35/1_MSN1048. 36 records from Total foraminifera counts of multinet FCA97C_MSN1339. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 27 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/041-5. 3 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 9 records from Nannofossil abundance of Hole 15-150. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 287 records from (Table 3) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-749B. 11 records from Foraminifera species abundances from tow TT011_2-MOC57. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-52. 157 records from Planktic foraminifera counts at CTD station PS55/063. 11 records from Microzooplankton abundance and biomass at station TT045_7-13. 8 records from Microplankton counts and carbon biomass at station TT012_5-CTD10. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 75 records from Microzooplankton abundance measured on water bottle samples at station PS58/009-2. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 180 records from Paul-Gerhardt-Schule Dassel. 78 records from Total foraminifera counts of multinet M12/3_MSN541. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 138 records from Plasm bearing foraminifera counts of multinet M21/2_MSN652. 69 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1379. 30 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5130-2. 55 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/590-1. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 11 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 431 records from (Table 6) Benthic foraminiferal community at DSDP Hole 94-611C. 4498 records from Flora of Japan Specimen Database. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 1 records from Microplankton counts and carbon biomass at station TT011_6-CTD71. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-15-5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 340 records from Phytoplankton abundance and species composition in the Gulf of Naples from February to December 1987. 2 records from Zetes laevigatus. 96 records from Pollen profile from Muscotah Marsh A. 2 records from Ostracoda abundance of Hole 13-129. 4 records from Nannofossil abundance of Hole 29-284A. 2 records from Nannofossil abundance of Hole 25-249. 842 records from (Table 3) Calcareous nannofossil distribution on ODP Hole 117-720A. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 85975 records from Mollusca specimens of Toyama Science Museum. 268 records from Geometry of coccolith Coccolithus pelagicus in sediment core PS1113-1. 101 records from Nannofossil abundance of Hole 64-476. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 7 records from Nannofossil abundance of Hole 6-55. 4 records from Nannofossil abundance of Hole 66-493A. 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 103 records from Mammals (UWEP-MM). 78 records from Mammals (GNHM-MM). 29 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 27 records from Smear slide analysis on sediment core GeoB4212-2. 2 records from Nannofossil abundance of Hole 3-13. 11 records from Nannofossil abundance of Hole 22-218. 79 records from (Table 2) Quarternary ostracod abundance in sediment core CRP-1. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 3855 records from Icota - Pelagant. 4778 records from SO-Polylist. 280 records from (Table 4) Occurrences of ostracodes in ODP Hole 122-763C. 52 records from (Table 2) Abundance of total planktonic foraminifera and Neogloboquadrina pachyderma in sediment core KNO5103-0029GGC. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 64 records from Establecimiento de la colección de levaduras marinas de México. 205599 records from CABI Bioscience Fungus Collection. 4288 records from Universitat de Girona: HGI-Cormophyta. 1098 records from Mushroom in North Korean (KIDR-MR). 1322 records from (Table 3) Percentages of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 218 records from Planktic foraminifera assemblage in sediment core GIK16396-1. 73 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 46 records from (Table 1) Distribution of planktic foraminifera in sediments from Core AMK4-410GC. 1241 records from (Appendix 2, Part 2) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-689. 1877 records from Odonata de la huasteca potosina (insecta). 1789 records from Computarización de la Colección de Microorganismos de importancia acuícola del CIAD, AC. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 950 records from (Table 9) Distribution of planktonic foraminifera in the early Pliocene to Holocene section of ODP Hole 149-900A. 178 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 6 records from Folklore and Natural History Museum Mammal. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6290 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 191 records from (Table 3) Distribution of principal species of benthic foraminifers in bottom sediments from Core LV28-42-5, Sea of Okhotsk. 29877 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 894 records from CNAN/Arañas sinantrópicas. 6602 records from Relative abundance of planktic foraminifera in sediment core GeoB1309-2. 188 records from Frauenholz (Holzmaden). 34 records from Occurrence of mammalia relicts at site Nikolaushöhle. 14 records from Radiolaria assemblage in sediment core GIK23259-2. 57 records from Planktic foraminifera abundance of Hole 84-566. 812 records from Planktic foraminifera abundance of Hole 94-607. 6454 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 3559 records from Actualización de bases de datos de peces. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 1200 records from Invertebrate specimens of Toyama Science Museum. 10789 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees. 2088 records from Benthic foraminifera of sediment core MD99-2286. 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 243 records from Memorial University Department of Biology Collection. 7939 records from Botany registration database by Danish botanists. 15455 records from Laboratorio de Entomología y Control de Plagas del Instituto Cavanilles de Biodiversidad y Biología Evolutiva de la Universidad de Valencia: ENV. 243 records from Point Pelee National Park Collection, Canada. 21619 records from Botanical Museum, Copenhagen. Database of type specimens. 146624 records from Plants of Papua New Guinea. 115365 records from TTU Mammals Collection. 1474 records from CCUG Microorganisms databases(Bacteria). 32606 records from TSB Lichen Herbarium. 783 records from RAVON (NL) - Fish observations extracted from Hoek (1890) and Redeke (1921). 477 records from (Table 3) Relative abundances of planktic foraminifera in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 976457 records from EURISCO, The European Genetic Resources Search Catalogue. 113 records from Stable isotope analysis on sediment core PS2644-2. 140 records from Distribution of planktic foraminifera of sediment core GIK23424-3. 900 records from Percentages of planktonic foraminifera species in sediment core V30-36. 429 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V32-128. 16122 records from Colección Herpetológica del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 186 records from (Table 2c) Percentages of energy flow of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 544 records from (Table AT6) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130B. 134 records from National Feral Ferret (Mustela putoris furo) Database. 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 24 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB04 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D2. 38 records from Occurrence of mammalia relicts at site Istalloskö. 24 records from Planktic foraminifera abundance of Hole 19-189. 10985533 records from Norwegian Species Observation Service. 118 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 25 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200260. 38 records from RSPB - Lesser Spotted Woodpecker sample survey in England 2007. 3 records from Planktic foraminifera abundance of Hole 54-424B. 156 records from Range table from planktonic foraminifers in ODP Hole 155-932B. 17 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (2000m section). 321 records from (Table T1) Dinoflagellate cyst abundance in ODP Hole 171B-1053A sediments. 46 records from (Table 6) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841B. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 6529 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 22 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 432 records from Foraminifera abundance of Hole 60-454. 584 records from Planktic foraminifera abundance of Hole 11-98. 1787 records from Planktic foraminifera abundance of Hole 80-548. 12612 records from (Table 1) Range table of planktonic foraminifers from ODP Hole 166-1006A sediments. 74 records from Range table from planktonic foraminifers in ODP Hole 167-1013A. 1649 records from Benthic foraminifera abundance of Hole 47-397. 136 records from Range table from benthic foraminifers in ODP Hole 192-1184A. 208 records from Range table from benthic foraminifers in ODP Hole 144-875C. 167 records from Range table from benthic foraminifers in ODP Hole 171-1049A. 288 records from Range table from planktonic foraminifers in ODP Hole 154-929E. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 401 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 264 records from Range table from benthic foraminifers in ODP Hole 146-892A. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 168 records from Phytoplankton abundance in surface water in September 1996, Pisco, Peru. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 47244 records from Collection Mollusca SMF. 17720 records from Collection Polychaeta SMF. 3439 records from MEXU/Flora de Oaxaca. 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 3207 records from UAFMC Herps. 336 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 45 records from NSG Dellwiger Wald, Dortmund. 61 records from Biosphärenreservat Münsinger Alb. 31747 records from Syrphids of Ireland. 31 records from First description of the worker caste of Nylanderia smythiesii (Hymenoptera: Formicidae). 132 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1 records from Oribates facula. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 10866 records from Heteroptera of Ireland. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 5056 records from Nest census, Windmill Islands 2002/03. 48243 records from Biological Records Centre - Millipede (Diplopoda) records for Britain and Ireland to 2005. 2222 records from UWYMV Bird Collection (Arctos). 406 records from (Table 4) Distribution of foraminifera in the Miocene section of ODP Hole 133-816C. 934 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Japanese Knotweed Survey. 275 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in Quaternary sediments from ODP Hole 189-1172A. 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 48 records from (Appendix) Abundance of Discoaster brouweri and Coccolithus pelagicus in ODP Site 180-1115 sediments. 58327 records from Inventaire National du Patrimoine Naturel : Fichier communal des ongulés. 4 records from Seodaemun Museum of Natural History Fossil. 2 records from Two new species of Baeus (Hymenoptera: Scelionidae) from southeastern Brazil parasitoids of Anelosimus (Araneae: Theridiidae).. 19 records from (Table T3) Calcareous nannofossil abundance of ODP Hole 189-1170A sediments. 2994 records from Museu de Ciències Naturals de Barcelona: BGJBB. 18 records from (Table 2) Abundance, wet biomass, and carbon biomass of all major groups and total phytoplankton in the upper and lower parts of the desalinated water lens and in the layer under the lens in the Kara Sea. 210 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Mimidae. 70 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 416 records from (Table 3) Benthic foraminiferal genera in DSDP Core 95-612-21-5 and 95-612-21-6. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 132 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fringillidae. 43 records from Relative abundance of planktic foraminifer Globigerinita uvula in core PS1243. 135 records from Collection Pisces - KAUMM. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 49362 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 6 records from Pollen profile RAA37, Lake Racou, France. 35 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty and Biswas. 1196 records from Entomological collection of the National Museum. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 40 records from BUND Naturschutzzentrum St. Julian. 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 1 records from Zetes dorsalis. 1605 records from Hare Survey of Ireland 06/07. 155892 records from Lund Museum of Zoology - Insect collections (MZLU). 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 56 records from Estetal (Buxtehude). 31 records from Düpenauwiesen. 46 records from Total foraminifera counts of multinet M6/7_MSN140. 202 records from Total foraminifera counts of multinet M6/7_MSN96. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 2174 records from MLZ Mammal Collection (Arctos). 38200 records from Herbario Universidad de Antioquia (HUA). 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007 . 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 38 records from Was lebt in der Brutzwiese?. 258 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 1 records from Zur Kenntnis der Lithobiiden. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 95
Keywords: GBIF; biodiversity; species occurrences